Características culturais da Petrobrás e da Eletrobrás que favorecem suas adaptabilidades - Sabino, João Marcos (1999)
This thesis is designed to explore, describe and analyze the characteristics of the Petrobras an Eletrobrás cultures in regard to their adaptabilities and conclude which of them could favor the adaptability of these companies. This dissertation has been developed from bibliografical research which identify the theoretical cultural characteristics of organizational adaptability, trom bibliografical research of the principal public policies that have influenced these companies and through interviews, in regard to their organizational cultures, whith persons attached to them.